Market Restrictions of Contracting Out the Public Service at the Municipal Level - Mikušová Meričková, Beáta; Mališová, Danieal; Murínová, Kristína (Springer Nature Switzerland AG, 2023)
Under contracting out as the alternative service delivery arrangement, a government retains responsibility for providing a service, but it hires private firms to produce and deliver it. The theory of contracting suggests that, provided certain conditions are met, contracting out has the potential to improve efficiency without sacrificing quality, compared to direct public production. In developed countries, contracting out can sometimes improve the performance of the public sector. In countries making the transition from planned to market-based economies, the situation is much more complicated. Outcomes of contracting out public service are determined by the quality of contract management, and also by the character of the market of contracted service. The aim of this chapter is to identify the scale of local public service contracting out and market constraints affecting its application. The study examines the experience with contracting out service of collection and disposal of municipal solid waste among 195 municipalities in Slovakia by primary research. The outcome of quantitative analysis suggests contracting out is a frequently used service delivery arrangement (88.26% of municipalities use contracting out waste collection and disposal services), however, the outcomes of contracting out can be affected by the high concentration of service market measured by indexes concentration ratio (CR) and Herfindahl–Hirshman index (HHI).
Tržní omezení zadávání veřejných služeb na úrovni obcí
Keywords: Alternative service delivery arrangements; Contracting out public services; Municipalities; Market concentration; Ujednání o poskytování alternativních služeb; poskytování veřejných služeb; obce; koncentrace trhu